ToF‐SIMS study of the surface of catalysts used in biomass valorization1. (21st January 2014) - Ruppert, A. M.; Grams, J.; Matras‐Michalska, J.; Chełmicka, M.; Przybysz, P.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> Hydrolytic hydrogenation of cellulose toward fuel additive – γ‐valerolactone (GVL) – has been studied, and the catalytic performance of Pt/TiO2 and Ru/TiO2 and reaction conditions were optimized. Additionally, new information about the changes of catalyst surface after the reactions of lignocelulose toward GVL was obtained. Two procedures were investigated: one‐pot hydrolysis‐hydrogenation and hydrolysis of cellulose followed by hydrogenation in two separate reactions. Spent catalysts were tested by time‐of‐flight SIMS (ToF‐SIMS). Reaction conditions strongly influence the GVL yield, which was much lower during one‐pot procedure where much higher carbon deposit and catalyst deactivation was observed by ToF‐SIMS and temperature‐programmed reduction. Ruthenium catalysts were more active than platinum ones in liquid phase reactions toward GVL, independently of the feedstock. Copyright © 2014 John Wiley & Sons, Ltd.